Method for preparing 4-propyl syringol by catalyzing hydrogenolysis of lignin through cobalt-nitrogen co-doped porous carbon

The one-pot preparation of cobalt-nitrogen co-doped porous carbon catalysts solves the problems of complex and high-cost catalyst preparation in high-value utilization of lignin, achieves highly selective catalytic hydrogenolysis of lignin under mild conditions, and prepares high-quality catalysts. Added value to 4-propylsyringyl alcohol.

CN119350133AActive Publication Date: 2025-01-24SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411393301.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-24
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The prior art has problems such as complex catalyst preparation, high cost and harsh reaction conditions in the high-value utilization of lignin, which affects the industrial application of technology.

Method used

Cobalt and nitrogen co-doped porous carbon catalysts are used to prepare catalysts with hierarchical porous structures through a one-pot method. Nitrogen elements are used to promote the capture and fixation of metallic cobalt to form CoN4 complexes and improve catalytic activity.

Benefits of technology

Under mild conditions, high-selective catalytic lignin hydrogen disintegration is achieved, and single-phenol chemicals, which are mainly 4-propyplacular alcohol. The transformation rate of lignin reaches 75.6-94.5 %, and the total revenue of single-phenols is 14.2 ~ 28.8WT. %, 4-propyplacular mellacant revenue was 4.1-9.9WT. %. The catalyst structure was stable and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350133A_ABST
    Figure CN119350133A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing 4-propyl syringol by catalyzing hydrogenolysis of lignin through cobalt-nitrogen co-doped porous carbon. According to the method, organic soluble lignin is taken as a raw material, lignin-based cobalt-nitrogen co-doped porous carbon is taken as a catalyst, small molecular alcohol is taken as a reaction medium, stirring reaction is performed under the hydrogen pressure of 1-2MPa and at the temperature of 190-260 DEG C, and the organic soluble lignin is selectively hydrogenolyzed into a monophenol chemical mainly containing 4-propyl syringol; the catalyst disclosed by the invention does not need to be subjected to carrier preparation, impregnation and reduction, and also does not need to be subjected to mofs material preparation and roasting, so that the catalyst has obvious advantages in a catalyst preparation process; according to the catalyst, transition metal is used as catalytic active metal, and the metal is uniformly dispersed on the surface of the catalyst in a monatomic-level dispersion degree to form a complex with CoN4 as a main component with carbon and nitrogen; the catalyst is wide in raw material source, low in metal content and obvious in cost advantage, and has the advantage of large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation of a highly dispersed metal catalyst and 4-propyl syringol, and in particular to a method for preparing monophenol from lignin with high selectivity by using a lignin-based cobalt-nitrogen co-doped porous carbon-supported highly dispersed cobalt catalyst, and belongs to the field of high-value utilization of biomass energy. Background Art

[0002] With the development of human society, the progress of science and technology is changing with each passing day. Behind the rapid development of science and technology, energy consumption is indispensable, but non-renewable fossil energy is still the main source of energy. With the development of society, environmental problems such as global warming and pollution are receiving more and more attention from people, and finding a green and renewable energy source has become a hot spot pursued by researchers from all over the world. The green energy discovered at this stage includes solar energy, wind energy, tidal energy and biomass energy. Compared with other green energy, biomass energy is not only rich in reserves, but also rich in various functional groups, can continuously and stably output energy, and can be converted into a variety of high value-added chemicals. Therefore, biomass energy is the best substitute for fossil energy.

[0003] As the most common form of biomass, lignocellulose is mainly composed of three parts: hemicellulose (20-30%), cellulose (20-30%) and lignin (10-35%). Among them, hemicellulose and cellulose as polymers of pentose and hexose have been industrially utilized. Lignin is difficult to be directly converted into the required chemicals due to its three-dimensional amorphous structure and complex linking bonds. However, as the only renewable aromatic structure in nature, the high-value utilization of lignin has always attracted much attention. After research, it was found that the structure of lignin is mainly composed of three phenylpropane structural units (H unit: p-hydroxyphenyl; G unit: guaiacol; S unit: eugenol) linked by a variety of different carbon-carbon bonds and carbon-oxygen bonds. The complex structure, large molecular volume and high dissociation energy of the linking bond are the main factors limiting the high-value utilization of lignin.

[0004] Compared with molecular sieves or metal oxide catalysts, carbon-supported catalysts are not only cheap and easy to obtain, but also highly modifiable. Among them, nitrogen-modified nitrogen-doped carbon catalysts not only provide a large number of active sites, which is more conducive to the loading of metals, but also enrich the defects on the surface of carbon materials, which is more conducive to the occurrence of reactions, making carbon-nitrogen catalysts excellent carriers for single-atom catalysts. Compared with traditional metal-supported catalysts, highly dispersed metal catalysts are more evenly distributed on the surface of the carrier, and the high dispersion of metal particles also leads to a higher specific surface energy, which further promotes the catalytic activity of the catalyst. However, the preparation method of single-atom highly dispersed metal catalysts is usually more complicated, and due to their higher specific surface energy, the metal is more likely to agglomerate during the catalytic reaction, causing it to be inactivated.

[0005] The structural formula of 4-propyl syringol is Because of its antioxidant properties and rich functional group structure, it is often widely used in the fields of food industry, pharmaceutical synthesis and bio-based materials. For example, researchers have observed that smoked food not only has a unique aroma, but also has a longer storage time at room temperature. Further in-depth investigation found that when using wood to smoke food, 2,6-dimethoxyphenol produced by wood pyrolysis adheres to the surface of food and has a good antioxidant effect. At the same time, in the field of medicine, 4-propyl eugenol is also one of the important intermediates of psychotropic drugs cannabinoid diphenol. In terms of materials, compared with other types of lignin derivatives, 4-propyl eugenol has more oxygen-containing functional groups and can be used as a precursor for biomass materials. Currently, 4-propyl eugenol in commercialization mainly uses petroleum-based products and is prepared through multi-step reactions. This preparation method faces challenges such as low selectivity of 4-propyl eugenol and complex reactions. Therefore, the use of renewable lignin resources to prepare 4-propyl eugenol by one-step hydrogenolysis is of great significance to the high value of lignin and is expected to replace existing organic synthetic chemistry technology.

[0006] Chinese invention patent application 202311762765.4 discloses a zirconium phosphate supported ruthenium-based catalyst Ru@RuO 2 Preparation method and hydrogenolysis of lignin and model compounds. 2 / N 2 , catalyzing the hydrogenolysis of dealkalized lignin at 250°C for 12 hours, a single benzene ring product of 23.9wt.% can be obtained. Although this technology has achieved a high yield of single benzene ring products, the selectivity of single products is low. In addition, this technology uses precious metals as the main active sites, which further increases the production cost of the catalyst. In particular, only part of the Ru in the catalyst is reduced to Ru elemental substance for catalytic action, which further reduces the metal utilization rate and affects the industrialization prospects of this technology.

[0007] Chinese invention patent 202111370517.6 discloses a method for lignin hydrogenolysis catalyzed by metal nickel supported on sodium lignin sulfonate porous carbon. This technology uses ZnCl 2 The carbon carrier with multi-level pore structure was prepared by using KOH and sodium lignin sulfonate as the pore-forming agent, and then loaded with metal Ni by wet impregnation method. The catalyst Ni / C was obtained after reduction under hydrogen atmosphere. LS-ZnK , at 230℃, 2MPa H 2Under the same conditions, the total yield of monophenols can be 22.03wt.% after 4h reaction, of which the yield of 4-propyl syringol is 7.4wt.%. Although this technology uses transition metals as active sites, the catalyst preparation requires multiple steps such as precursor mixing, high-temperature roasting, washing, impregnation, and reduction. The preparation process is relatively complicated, which affects industrial application.

[0008] Chinese invention patent application 202311873995.8 discloses a method for preparing monophenolic chemicals by catalyzing the depolymerization of lignin with a derivative of a zeolite imidazolate skeleton material. This technical study uses ZIF-67 as a catalyst precursor and pyrolyzes it to obtain the catalyst Co@NC. In the process of catalytic hydrogenolysis of lignin by Co@NC-800, a total yield of monophenols of up to 16.1wt.% and 7.4wt.% of 4-propyl syringol can be obtained under the conditions of 100mg lignin, 125mg catalyst, 230℃, and 1MPaAr. However, due to the large-scale decomposition of the 2-methylimidazole ligand during the pyrolysis process, the metal content in the catalyst is greatly increased, and the cobalt content in the Co@NC-800 catalyst reaches 29.0wt.%. The increase in metal content without dispersion measures leads to metal agglomeration, a reduction in the exposed surface of active metals, a reduction in the utilization rate of metals, an increase in the implementation cost of the technology, and an impact on the industrial application of the technology. Summary of the invention

[0009] Aiming at the problems encountered in the current high-value-added lignin, such as large lignin molecular volume, hindered reaction mass transfer, complex linking bonds, high bond energy, complex catalyst preparation and high cost, which affect the industrial application of technology; the present invention provides a catalyst preparation process and cost have obvious advantages, which is conducive to large-scale production of a carbon-nitrogen catalyst with a multi-level pore structure loaded with highly dispersed transition metal cobalt, and can achieve highly selective catalytic lignin hydrogenolysis to prepare monophenol chemicals mainly composed of 4-propyl syringol under mild conditions; wherein the lignin raw material conversion rate reaches 75.6-94.5%, the total yield of monophenol products reaches 14.2-28.8wt.%, and the yield of 4-propyl syringol alone reaches 4.1-9.9wt.%.

[0010] The purpose of the present invention is achieved through the following technical solutions:

[0011] A method for preparing 4-propyl syringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon, using organic soluble lignin as a raw material, lignin-based cobalt-nitrogen co-doped porous carbon as a catalyst, and small molecule alcohol as a reaction medium, stirring the reaction at a hydrogen pressure of 1 to 2 MPa and a temperature of 190 to 260° C., and selectively hydrogenating the organic soluble lignin into monophenolic chemicals mainly composed of 4-propyl syringol;

[0012] The lignin-based cobalt-nitrogen co-doped porous carbon is obtained by mixing a precursor and an alkaline pore-forming agent, calcining the mixture in an inert atmosphere at 800-1000° C., cooling, grinding, washing and drying. The precursor is prepared by stirring and dissolving a carbon source and a nitrogen source in deionized water at 60-80° C., adding zinc salt, potassium salt and cobalt salt dissolved in deionized water, stirring at 60-80° C., hydrothermally reacting at 160-200° C. for 8-10 hours, cooling and drying. The carbon source is any one of sulfate lignin, alkali lignin or sodium lignin sulfonate. The nitrogen source is any one of dicyandiamide and melamine.

[0013] To further achieve the purpose of the present invention, preferably, the zinc salt is any one of zinc acetate, zinc chloride and zinc nitrate;

[0014] The potassium salt is any one of potassium acetate, potassium chloride and potassium nitrate;

[0015] The cobalt salt is any one of cobalt acetate and cobalt chloride.

[0016] Preferably, the mass ratio of the carbon source to the nitrogen source is 1:3 to 1:5; the mass ratio of the carbon source to the cobalt salt is 1:0.13 to 1:0.62; the mass ratio of the carbon source to the zinc salt is 1:0.33 to 1:0.66; the mass ratio of the carbon source to the potassium salt is 1:0.15 to 1:0.30; the zinc salt, potassium salt and cobalt salt dissolved in deionized water form a metal salt aqueous solution, in which the concentration of total metal ions in water is 50 mmol L -1 ~300mmol L -1 .

[0017] Preferably, the stirring reaction time at a temperature of 190-260° C. is 2-10 h; the alkaline pore-forming agent is any one or more of KOH and NaOH; the mass ratio of the carbon source to the alkaline pore-forming agent is 1:0.25-1:0.75; and the stirring time at 60-80° C. is 8-10 h.

[0018] Preferably, the cooling involved in the cooling, grinding, washing and drying after calcination at 800-1000°C in an inert atmosphere refers to cooling to room temperature, the grinding involved refers to grinding to a uniform powder without obvious granularity, and the washing involved includes water washing and acid washing. The water washing refers to dispersing the ground product in deionized water, stirring for 2-4 hours, filtering, and then washing the solid with a large amount of water until the filtrate is neutral; the acid washing refers to dispersing the washed product in an aqueous solution of an inorganic acid, stirring for 2-4 hours, filtering to obtain a solid, and then washing the solid with deionized water until the filtrate is neutral; the acid used for the acid washing is any one of sulfuric acid, nitric acid and hydrochloric acid, and the concentration of the acid is 1-2 mol L -1The drying involved is to dry the washed solid in an oven at 50-80°C for 8-12 hours to constant weight.

[0019] The cooling and drying after the hydrothermal reaction at 160-200°C for 8-10 hours refers to cooling to room temperature, and the drying refers to completely removing water in a rotary evaporator at 40-60°C. After the rotary evaporation, the solid obtained is dried in an oven at 50-80°C for 8-12 hours to constant weight; the oven is a forced air drying oven.

[0020] Preferably, the inert atmosphere is any one of nitrogen, argon and helium.

[0021] Preferably, the calcination is carried out in an extractable vacuum tube furnace; the hydrothermal kettle used for the hydrothermal reaction is a lined stainless steel hydrothermal reaction kettle, which is equipped with a stirrer and is stirred and heated in an oil bath.

[0022] Preferably, the organosoluble lignin is obtained by the following extraction method: mixing biomass powder with an extract, reacting at 90-110° C. for 2-4 hours, and cooling to room temperature; filtering to obtain an organic filtrate, adding deionized water to precipitate a solid, filtering and drying to obtain the organosoluble lignin.

[0023] Preferably, the biomass is derived from any one of bagasse, wheat bran, corn cob, bamboo, birch and poplar; the extract is a mixture of acid and organic solvent; the organic solvent is any one of dioxane and ethanol; the drying after filtration is carried out in a vacuum drying oven at a drying temperature of 40-60°C.

[0024] Preferably, the acid is 1 to 2 mol L -1 any one of hydrochloric acid and sulfuric acid solutions; the ratio of the mass of the biomass powder to the volume of the organic solvent in the extract is 1:3 to 1:5, and the units of mass and volume are g and mL respectively; the ratio of the mass of the biomass powder to the volume of the acid solution is 1:0.8 to 1:1, and the units of mass and volume are g and mL respectively.

[0025] Preferably, the monophenol chemicals include: H units (4-ethylphenol and ethyl dihydro-p-coumarate), G units (4-ethylguaiacol, 4-propylguaiacol and ethyl dihydroferulate) and S units (4-propylsyringol).

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] 1) Compared with the single-atom catalyst preparation methods in the prior art, such as impregnation method, coprecipitation method and MOFs precursor method, the catalyst of the present invention is prepared by a one-pot method, which has a simple preparation process, high repeatability, and can achieve large-scale production. Moreover, the metal loading in the present invention can be as low as 0.46wt.%, and the highly exposed active sites not only improve the conversion rate of lignin, but also improve the selectivity of the product. The maximum yield of the main product 4-propyl syringol can reach 9.9wt.%, and the selectivity can reach 28.9-39.1%. Compared with most current lignin conversion technologies, this technical condition is mild, and the product yield can reach the highest when the reaction temperature is 230°C and the hydrogen pressure is 1MPa. The catalyst structure is stable, and after repeated use, its catalytic activity can be restored by simple steam regeneration.

[0028] The medium-strong acid on the surface of the catalyst of the present invention forms a coordinated catalytic effect with the cobalt in the catalytic active center, which promotes the cracking reaction of the abundant β-O-4 bonds in the lignin in the carbon center free radical path. The coordinated effect reduces the reaction activation energy, improves the conversion rate of lignin and the selectivity of monophenol products. Compared with the prior art, which generally has dozens of lignin depolymerization products, only six main monophenol products are produced after the reaction, and the products can be separated by simple column chromatography to obtain 8.3wt.% of 4-propyl syringol, and the product purity is >99%.

[0029] 2) Compared with the prior art molecular sieves and metal oxide catalysts, the catalyst CoNC used in the present invention is low in cost, wherein the carbon source mainly comes from industrial papermaking waste, which is difficult to be used in a high-value manner. The nitrogen source is any one of dicyandiamide or melamine, which is widely used as a fertilizer and fine chemical with a large output and a price advantage. The metal cobalt as an active site is a transition metal element, which has a larger reserve in the earth than precious metals and is easier to industrialize, especially when the content of metal cobalt in the catalyst of the present invention is low. The catalyst prepared using the precursor of the present invention has a larger specific surface area and a multi-level pore structure, which can enhance the mass transfer effect, and with the uniformly dispersed active sites (single atoms and sub-nanometer clusters), the effective contact between the substrate and the active site can be promoted to a greater extent.

[0030] 3) Compared with the single-atom catalyst preparation methods in the prior art, such as impregnation method, coprecipitation method and MOFs precursor method, the catalyst of the present invention is prepared by a one-pot method, which has a simple preparation process, high repeatability, and can achieve large-scale production. Moreover, the metal loading in the present invention can be as low as 0.46wt.%, and the highly exposed active sites not only improve the conversion rate of lignin, but also improve the selectivity of the product. The maximum yield of the main product 4-propyl syringol can reach 9.9wt.%, and the selectivity can reach 28.9-39.1%. Compared with most current lignin conversion technologies, this technical condition is mild, and the product yield can reach the highest when the reaction temperature is 230°C and the hydrogen pressure is 1MPa. The catalyst structure is stable, and after repeated use, its catalytic activity can be restored by simple steam regeneration.

[0031] 4) The nitrogen element in the technology of the present invention not only promotes the capture and fixation of metal cobalt by the catalyst carrier, but also forms CoN 4 The electron transfer from nitrogen atoms to cobalt atoms can change the electronic microenvironment of the metal cobalt surface and promote its catalytic effect on lignin hydrogenolysis. 4 The active site has the highest adsorption energy for the S unit in lignin, which is one of the reasons for the high selectivity of the 4-propylsyringol product.

[0032] 5) The lignin used in the present invention is derived from non-food biomass such as agricultural waste, and the monophenol products mainly composed of 4-propyl syringol prepared by catalyzing the hydrogenolysis of lignin have high commercial value. At the same time, the main carbon source of the catalyst also comes from papermaking waste, so the technology follows the idea of ​​carbon cycle. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is N of the catalyst in Examples 1-4 of the present invention 2 Isothermal adsorption-desorption curves.

[0034] Figure 2 It is the surface pore size distribution diagram of the catalyst in Examples 1-4 of the present invention.

[0035] Figure 3 is a SEM image of the catalyst in Example 1 of the present invention.

[0036] Figure 4 is a SEM image of the catalyst in Example 2 of the present invention.

[0037] Figure 5 is a SEM image of the catalyst in Example 3 of the present invention.

[0038] Figure 6 is a SEM image of the catalyst in Example 4 of the present invention.

[0039] Figure 7 It is the XRD diagram of the catalyst in Examples 1-4 of the present invention.

[0040] Figure 8 The catalyst CoNC in Example 4 of the present invention -M4 Spherical aberration scanning transmission electron microscopy image.

[0041] Fig. 9 The catalyst CoNC in Example 4 of the present invention -M4 Synchrotron radiation near-edge absorption curve.

[0042] Fig.10 The catalyst CoNC in Example 4 of the present invention -M4 Synchrotron radiation Fourier transform X-ray absorption fine structure spectroscopy.

[0043] Fig.11 The catalyst CoNC in Example 4 of the present invention -M4 Synchrotron radiation R spatial fitting of Fourier transform X-ray absorption fine structure spectra.

[0044] Fig.12 The catalyst CoNC in Example 4 of the present invention -M4 Surface active sites CoN 4 Calculation of adsorption energy for the basic structural units of lignin, H, G and S units.

[0045] Fig.13 These are the six monophenol products produced by catalytic hydrogenolysis of lignin in Example 5 of the present invention.

[0046] Fig.14 This is the mass spectrum of 4-propylsyringol, the main product of lignin hydrogenolysis in Example 5 of the present invention. DETAILED DESCRIPTION

[0047] In order to better understand the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments, but the embodiments of the present invention are not limited thereto.

[0048] The invention discloses a method for preparing 4-propyl syringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon. The method comprises the following steps: using organic soluble lignin as a raw material, lignin-based cobalt-nitrogen co-doped porous carbon as a catalyst, and small molecule alcohol as a reaction medium. The method comprises stirring and reacting the organic soluble lignin at a hydrogen pressure of 1 to 2 MPa and a temperature of 190 to 260° C. to selectively hydrogenolyze the organic soluble lignin into monophenolic chemicals mainly composed of 4-propyl syringol. The lignin-based cobalt-nitrogen co-doped porous carbon is prepared by mixing a precursor with an alkaline pore-forming agent at 800 to 260° C. The precursor is prepared by cooling, grinding, washing and drying after calcination at 1000°C in an inert atmosphere; the precursor is prepared by stirring and dissolving a carbon source and a nitrogen source in deionized water at 60-80°C; adding zinc salt, potassium salt and cobalt salt dissolved in deionized water, stirring at 60-80°C, hydrothermally reacting at 160-200°C for 8-10h, cooling and drying; the carbon source is any one of sulfate lignin, alkali lignin or sodium lignin sulfonate; the nitrogen source is any one of dicyandiamide and melamine.

[0049] The invention is characterized in that sodium lignin sulfonate, sulfate lignin or alkali lignin, waste from the papermaking industry, is used as a carbon source, and dicyandiamide or melamine, which is relatively low in cost, is used as a nitrogen source, and a cobalt-nitrogen co-doped carbon-nitrogen catalyst with multi-level pores is prepared by a one-pot method. Such catalyst preparation does not require the preparation of a carrier-impregnation-reduction process, nor does it require the preparation of MOFs materials and then roasting, which has obvious advantages in the catalyst preparation process. The prepared catalyst mesoporous structure is more conducive to the adsorption of lignin substrates, strengthens the mass transfer effect, and increases the substrate conversion rate; and highly dispersed cobalt exists in the form of single atoms and sub-nanometer clusters, and the uniformly dispersed active sites also greatly improve the selectivity of the product, selectively break the ether bonds and ester bonds in lignin, and improve the selectivity of monophenol products, wherein the catalyst cobalt metal content is 0.46-10.88wt.%, the metal content is low, and it has obvious cost advantages.

[0050] Example 1: Lignin-based cobalt-nitrogen co-doped porous carbon catalyst CoNC -M1 Preparation

[0051] (1) 0.75 g of cobalt acetate (3 mmol), 0.58 g of potassium acetate (5 mmol) and 1.10 g of zinc acetate (5 mmol) were weighed and dissolved in 20 mL of deionized water, and the mixed solution was named solution A. In addition, 2 g of sodium lignin sulfonate and 8 g of dicyandiamide were weighed and dissolved in 30 mL of deionized water, and the mixed solution was named solution B. Solution A was kept ultrasonically at room temperature for 40 min and then slowly added dropwise to solution B. The mixed solution AB was stirred at 80°C for 8 h.

[0052] (2) The mixed solution AB was subjected to rotary evaporation at 60°C to remove the solvent to obtain a catalyst precursor solid, which was dried in a forced air drying oven at 80°C to constant weight. After drying, the solid was transferred to a 50 mL quartz boat and placed in a vacuum tube furnace and heated to 900°C for calcination for 2 h at a heating rate of 2°C / min.

[0053] (3) After the calcination, wait for the tube furnace to cool to room temperature, take out the black solid and wash the solid with 3×100 mL of deionized water. Then disperse the black solid into 30 mL of 1 mol L -1 The mixture was stirred in a sulfuric acid aqueous solution at room temperature for 2 h. After stirring, it was filtered and the black solid was washed with deionized water until the filtrate was neutral. After drying at 80 °C for 10 h, the lignin-based cobalt-nitrogen co-doped porous carbon catalyst CoNC was obtained. -M1 .

[0054] The Co content in the catalyst was determined to be 1.03 wt.% by ICP-AES. -M1 Perform N 2 Physical adsorption and desorption tests, such as Figure 1 As shown, CoNC -M1 Catalyst N 2 The adsorption-desorption curves conform to the IV type curve, indicating that CoNC -M1 There is a mesoporous structure in Figure 2 It can be seen that CoNC -M1 The pore distribution of the catalyst is still concentrated in the micropore area (<2nm). According to the pore volume calculation, CoNC -M1 The mesoporosity of the Figure 3 The same phenomenon can be observed in CoNC -M1 The catalyst surface is smooth and has no obvious pore structure. At the same time, there is no obvious gap between the catalyst layers. This corresponds to its relatively low specific surface area and a small amount of mesoporous structure. XRD characterization of the catalyst revealed that Figure 7 As shown, CoNC -M1 The catalyst has no obvious metal peak. Combined with the metal content, it can be inferred that Co is in the catalyst CoNC -M1 The surface is evenly dispersed without agglomeration.

[0055] Example 2: Catalyst CoNC -M2 Preparation

[0056] (1) 0.75 g of cobalt acetate (3 mmol), 0.58 g of potassium acetate (5 mmol) and 1.10 g of zinc acetate (5 mmol) were weighed and dissolved in 20 mL of deionized water, and the mixed solution was named solution A. In addition, 2 g of sodium lignin sulfonate and 8 g of dicyandiamide were weighed and dissolved in 30 mL of deionized water, and the mixed solution was named solution B. Solution A was kept under ultrasonication for 40 min at room temperature and then slowly added dropwise to solution B. The mixed solution AB was stirred at 80°C for 8 h. After stirring, it was transferred to a 100 mL hydrothermal kettle and stirred for hydrothermal treatment at 200°C for 10 h.

[0057] (2) The mixed solution AB was subjected to rotary evaporation at 60°C to remove the solvent. A catalyst precursor solid was obtained, and the solid was dried in a forced air drying oven at 80°C to constant weight. After drying, it was transferred to a 50 mL quartz boat, placed in a vacuum tube furnace, heated to 900°C, and calcined for 2 h at a heating rate of 2°C / min.

[0058] (3) After the calcination, wait for the tube furnace to cool to room temperature, take out the black solid and wash the solid with 3×100 mL of deionized water. Then disperse the black solid into 30 mL of 1 mol L -1 The mixture was stirred in a sulfuric acid aqueous solution at room temperature for 2 h. After stirring, the mixture was filtered and the black solid was washed with deionized water until the filtrate was neutral. The catalyst CoNC was obtained after drying at 80 °C for 10 h. -M2 .

[0059] The Co content in the catalyst was determined to be 1.80 wt.% by ICP-AES. -M1 Perform N 2 Physical adsorption and desorption tests, such as Figure 1 As shown, CoNC -M2 Catalyst N 2 The adsorption-desorption curves conform to the IV type curve, indicating that CoNC -M1 There is a mesoporous structure in Figure 2 It can be seen that CoNC -M2 The pore size distribution of the catalyst has begun to show a mesoporous structure (2nm<mesopore<50nm). According to the pore volume calculation, CoNC -M2 The mesoporosity of the nanostructured carbon nanotubes reaches 77.5%. Figure 4 It can be observed that a small amount of pores appear on the catalyst surface, and the catalyst edge is folded, and graphitization occurs. XRD characterization of the catalyst revealed that Figure 7 As shown, CoNC -M2 The catalyst has no obvious metal peak, which can be inferred that Co is in the catalyst CoNC -M2 The surface is evenly dispersed without agglomeration. -M2In the XRD pattern, an obvious peak appears at 26.2°, which represents the (002) plane of graphite.

[0060] Example 3: Catalyst CoNC -M3 Preparation

[0061] (1) 0.75 g of cobalt acetate (3 mmol), 0.58 g of potassium acetate (5 mmol) and 1.10 g of zinc acetate (5 mmol) were weighed and dissolved in 20 mL of deionized water, and the mixed solution was named solution A. In addition, 2 g of sodium lignin sulfonate, 8 g of dicyandiamide and 1 g of KOH were weighed and dissolved in 30 mL of deionized water, and the mixed solution was named solution B. Solution A was kept under ultrasonication for 40 min at room temperature and then slowly added dropwise to solution B. The mixed solution AB was stirred at 80°C for 8 h. After stirring, it was transferred to a 100 mL hydrothermal kettle and stirred and hydrothermally treated at 200°C for 10 h.

[0062] (2) The mixed solution AB was subjected to rotary evaporation at 60°C to remove the solvent. A catalyst precursor solid was obtained, and the solid was dried in a forced air drying oven at 80°C to constant weight. After drying, it was transferred to a 50 mL quartz boat and placed in a vacuum tube furnace and heated to 900°C for calcination for 2 h at a heating rate of 2°C / min.

[0063] (3) After the calcination, wait for the tube furnace to cool to room temperature, take out the black solid and wash the solid with 3×100 mL of deionized water. Then disperse the black solid into 30 mL of 1 mol L -1 The mixture was stirred in a sulfuric acid aqueous solution at room temperature for 2 h. After stirring, the mixture was filtered and the black solid was washed with deionized water until the filtrate was neutral. The catalyst CoNC was obtained after drying at 80 °C for 10 h. -M3 .

[0064] The Co content in the catalyst was determined to be 10.88 wt.% by ICP-AES. -M1 Perform N 2 Physical adsorption and desorption tests, such as Figure 1 As shown, CoNC -M3 Catalyst N 2 The adsorption-desorption curves conform to the IV type curve, indicating that CoNC -M3 There is a mesoporous structure in Figure 2 It can be seen that CoNC -M3 The catalyst has a distinct mesoporous structure (2nm<mesopore<50nm). According to the pore volume calculation, CoNC -M3 The mesoporosity of the nanostructured carbon nanotubes reaches 78.8%. Figure 5It can be observed that a large number of irregular pore structures appeared on the catalyst surface, and the catalyst showed obvious layered structure and graphitization. At the same time, SEM showed that CoNC -M3 A large number of regular cubes are attached to the surface. XRD characterization of the catalyst revealed that Figure 7 As shown, CoNC -M3 The catalyst has obvious peaks, corresponding to the (002) plane of graphite and Co 3 [Co(CN) 6 ] 2 The (200), (220) and (400) faces of Co 3 [Co(CN) 6 ] 2 It is usually used as a dye and adsorbent, but has no catalytic effect on hydrogenolysis, so it is presumed not to be an active site.

[0065] Example 4: Catalyst CoNC -M4 Preparation

[0066] (1) 0.75 g of cobalt acetate (3 mmol), 0.58 g of potassium acetate (5 mmol) and 1.10 g of zinc acetate (5 mmol) were weighed and dissolved in 20 mL of deionized water, and the mixed solution was named solution A. In addition, 2 g of sodium lignin sulfonate and 8 g of dicyandiamide were weighed and dissolved in 30 mL of deionized water, and the mixed solution was named solution B. Solution A was kept under ultrasonication for 40 min at room temperature and then slowly added dropwise to solution B. The mixed solution AB was stirred at 80°C for 8 h. After stirring, it was transferred to a 100 mL hydrothermal kettle and stirred for hydrothermal treatment at 200°C for 10 h.

[0067] (2) The mixed solution AB was subjected to rotary evaporation at 60°C to remove the solvent. The catalyst precursor solid was obtained and dried in a forced air drying oven at 80°C to constant weight. After drying, the solid mixture was ground evenly with 1g of KOH, and the solid mixture was transferred to a 50mL quartz boat and placed in a vacuum tube furnace and heated to 900°C for calcination for 2h at a heating rate of 2°C / min.

[0068] (3) After the calcination, wait for the tube furnace to cool to room temperature, take out the black solid and wash the solid with 3×100 mL of deionized water. Then disperse the black solid into 30 mL of 1 mol L -1 The mixture was stirred in a sulfuric acid aqueous solution at room temperature for 2 h. After stirring, the mixture was filtered and the black solid was washed with deionized water until the filtrate was neutral. The catalyst CoNC was obtained after drying at 80 °C for 10 h. -M4 .

[0069] The Co content in the catalyst was determined to be 0.46 wt.% by ICP-AES.-M4 Perform N 2 Physical adsorption and desorption tests, such as Figure 1 As shown, CoNC -M4 Catalyst N 2 The adsorption-desorption curves conform to the IV type curve, indicating that CoNC -M4 There is a mesoporous structure in Figure 2 It can be seen that CoNC -M4 The catalyst has a distinct mesoporous structure (2nm<mesopore<50nm). According to the pore volume calculation, CoNC -M4 The mesoporosity is as high as 92.9%. Figure 6 It can be observed that a large number of irregular pore structures appear on the catalyst surface, and the catalyst has an obvious layered structure with obvious graphitization. XRD characterization of the catalyst revealed that Figure 7 As shown, CoNC -M4 The catalyst has a more obvious graphite peak, corresponding to the (002) plane of graphite. Figure 8 Spherical aberration scanning transmission electron microscopy shows that most of the cobalt metal exists in the form of single atoms (atomic diameter <0.1nm) on the catalyst surface, and a small part of the metal exists in the form of sub-nano clusters (cluster diameter <1nm), proving that the cobalt metal is highly dispersed on the catalyst surface, so CoNC is not visible in XRD. -M4 The metal peak crystal phase, and the high dispersion of cobalt in the active center also promote the high selectivity of the catalyst for catalytic ether bond cleavage. Fig. 9 It can be seen that CoNC -M4 The valence state of Co in the catalyst is close to +2, and there is an obvious peak at 7714 eV, which represents the electronic transition from 1s to 4p. This phenomenon indicates that CoN appears in the catalyst. 4 Plane structure. Fig.10 It can be observed more intuitively that the catalyst CoNC -M4 The R space mainly appears (Co-N) and a small amount of (Co-Co) peak indicates that the main coordination element of Co in the catalyst is N. Fig.11 As shown in the figure, further fitting of the R space revealed that Co and N are in the form of CoN 4 Form exists, and Fig. 9 The conclusions are consistent and also verify Figure 8 The conclusion of spherical aberration electron microscopy is that Co in the catalyst exists mainly in the form of single atoms. 4 As the catalytic active center, the chemical adsorption energy is theoretically calculated based on H, G and S type model compounds. Fig.12 As shown, the S-type model compound is 4The adsorption energy at the site is the strongest, which is one of the main reasons why the selectivity of S unit products among lignin-derived monophenol products is the highest.

[0070] Example 5: CoNC -M4 Catalytic Hydrogenolysis of Organosoluble Bagasse Lignin

[0071] (1) Lignin extraction: Place the bagasse in a 60°C forced air drying oven and dry for 12 hours. The dried bagasse is crushed with a pulverizer and then sieved through a 60-mesh sieve. Weigh 10 g of the sieved bagasse powder, 10 mL of concentrated hydrochloric acid and 120 mL of 1,4-dioxane into a pressure bottle, stir and react at 100°C for 4 hours, and immediately cool to room temperature after the reaction. Filter to remove the residue, wash the filter cake with dioxane, combine the filtrate, add deionized water to precipitate the solid, filter and dry to obtain organic-soluble bagasse lignin.

[0072] (2) Catalytic lignin hydrogenolysis: Weigh 0.1 g of organosoluble bagasse lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0073] The GCMS used an FBX-5MS column (30 m × 0.25 μm × 0.25 mm). The instrument was kept at 50 °C for 1 min, then heated to 250 °C at a rate of 10 °C / min and kept there for 10 min. Fig.13 As shown in the GCMS analysis, there are only 6 main classification products, namely 4-ethylphenol, dihydro-p-coumaric acid ethyl ester, 4-ethylguaiacol, 4-propylguaiacol, dihydroferulate ethyl ester, 4-propyl syringol. The mass spectrum of the main product 4-propyl syringol is shown in Fig.14 As shown, it reflects that the main product is indeed 4-propylsyringol, and the NMR spectrum can also be attached to further confirm the structure of the substance.

[0074] Table 1 Summary of lignin hydrogenolysis monophenol products

[0075]

[0076]

[0077] The calculation formula of lignin conversion rate and monophenol product yield is shown in the following formula, wherein the conversion rate of lignin is calculated based on the mass comparison of recycled lignin and initial lignin (Equation 1). The yield of monophenol is determined according to the mass of monophenol product and the mass of initial lignin (Equation 2). The selectivity of monophenol product is determined by the weight percentage of the mass of a single product in the total monophenol (Equation 3).

[0078]

[0079] Where m o 、m Re 、m p 、Yield p and Yield Total Represent the initial lignin mass, the regenerated lignin mass, the single product yield and the total product yield respectively. The total yield of the monophenol product is 28.8wt.%, and the yield of the S unit product 4-propyl syringol is the highest among the single products, which can reach 9.9wt.%, and its selectivity can reach 34.4%. Through simple column chromatography separation, a 4-propyl syringol product with a yield of 8.3wt% can be obtained, and the purity can reach more than 99%. In CoNC -M4 Under catalysis, the lignin conversion rate can reach 94.5%.

[0080] Example 6: CoNC -M1 Catalytic hydrogenolysis of bagasse lignin

[0081] The difference between this implementation case and implementation case 5 is that:

[0082] Weigh 0.1 g of organosoluble bagasse lignin and 0.1 g of CoNC -M1 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0083] The calculation shows that the lignin conversion rate is 75.6%, the yield of monophenol products is 14.2 wt.%, of which the yield of 4-propyl syringol is 4.1 wt.%, and the selectivity can reach 28.9%.

[0084] Example 7: CoNC -M2 Catalytic Hydrogenolysis of Organosoluble Bagasse Lignin

[0085] The difference between this implementation case and implementation case 5 is that:

[0086] Weigh 0.1 g of organosoluble bagasse lignin and 0.1 g of CoNC -M2 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0087] The calculation shows that the lignin conversion rate is 82.4%, the yield of monophenol products is 19.2 wt.%, of which the yield of 4-propyl syringol is 7.5 wt.%, and the selectivity can reach 39.1%.

[0088] Example 8: CoNC -M3 Catalytic Hydrogenolysis of Organosoluble Bagasse Lignin

[0089] The difference between this implementation case and implementation case 5 is that:

[0090] Weigh 0.1 g of organosoluble bagasse lignin and 0.1 g of CoNC -M3 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0091] The calculation shows that the lignin conversion rate is 94.4%, the yield of monophenol products is 21.2 wt.%, of which the yield of 4-propyl syringol is 7.9 wt.%, and the selectivity can reach 37.3%.

[0092] Example 9: CoNC -M4 Catalytic Hydrogenolysis of Organosoluble Birch Lignin

[0093] The difference between this implementation case and implementation case 5 is that:

[0094] (1) Lignin extraction: Weigh 10 g birch powder, 10 mL concentrated hydrochloric acid and 120 mL 1,4-dioxane respectively and add them into a pressure bottle in sequence. Stir and react at 100°C for 4 h. After the reaction, cool to room temperature immediately. Filter to remove the residue, wash the filter cake with dioxane, combine the filtrate, add deionized water to precipitate the solid, filter and dry to obtain the organic soluble birch lignin.

[0095] (2) Catalytic lignin hydrogenolysis: Weigh 0.1 g of organic birch lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0096] The yield of monophenol product was calculated to be 19.6 wt.%, of which the yield of 4-propyl syringol was 8.0 wt.%, and the selectivity was up to 40.8%.

[0097] Example 10: CoNC -M4 Catalytic Hydrogenolysis of Organosoluble Poplar Wood Lignin

[0098] The difference between this implementation case and implementation case 5 is that:

[0099] (1) Lignin extraction: Weigh 10 g of poplar wood powder, 10 mL of concentrated hydrochloric acid and 120 mL of 1,4-dioxane respectively and add them into a pressure bottle in sequence. Stir and react at 100°C for 4 h. After the reaction is completed, cool to room temperature immediately. Filter to remove the residue, wash the filter cake with dioxane, combine the filtrate, add deionized water to precipitate the solid, filter and dry to obtain organic-soluble poplar wood lignin.

[0100] (2) Catalytic lignin hydrogenolysis: Weigh 0.1 g of organic soluble poplar lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0101] The yield of monophenol product was calculated to be 17.3 wt.%, of which the yield of 4-propyl syringol was 7.4 wt.%, and the selectivity was up to 42.8%.

[0102] Example 11: CoNC -M4 Catalytic Hydrogenolysis of Organosoluble Wheat Bran Lignin

[0103] The difference between this implementation case and implementation case 5 is that:

[0104] (1) Lignin extraction: Weigh 10 g of wheat bran powder, 10 mL of concentrated hydrochloric acid and 120 mL of 1,4-dioxane respectively and add them into a pressure bottle in sequence. Stir and react at 100°C for 4 h. After the reaction is completed, cool to room temperature immediately. Filter to remove the residue, wash the filter cake with dioxane, combine the filtrate, add deionized water to precipitate the solid, filter and dry to obtain the organosoluble wheat bran lignin.

[0105] (2) Catalytic lignin hydrogenolysis: Weigh 0.1 g of organosoluble wheat bran lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0106] The yield of monophenol product was calculated to be 11.6 wt.%, of which the yield of 4-propyl syringol was 3.4 wt.%, and the selectivity was up to 29.3%.

[0107] Example 12: CoNC -M4 Catalytic Hydrogenolysis of Organosoluble Bamboo Lignin

[0108] The difference between this implementation case and implementation case 5 is that:

[0109] (1) Lignin extraction: Weigh 10 g of bamboo powder, 10 mL of concentrated hydrochloric acid and 120 mL of 1,4-dioxane respectively and add them into a pressure bottle in sequence. Stir and react at 100°C for 4 h. After the reaction is completed, cool to room temperature immediately. Filter to remove the residue, wash the filter cake with dioxane, combine the filtrate, add deionized water to precipitate the solid, filter and dry to obtain organic soluble bamboo lignin.

[0110] (2) Catalytic lignin hydrogenolysis: Weigh 0.1 g of organic soluble bamboo lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0111] The yield of monophenol product was calculated to be 19.0 wt.%, of which the yield of 4-propyl syringol was 7.2 wt.%, and the selectivity was up to 37.9%.

[0112] Example 13: CoNC -M4 Catalytic Hydrogenolysis of Organosoluble Corncob Lignin

[0113] The difference between this implementation case and implementation case 5 is that:

[0114] (1) Lignin extraction: Weigh 10 g corncob powder, 10 mL concentrated hydrochloric acid and 120 mL 1,4-dioxane respectively and add them into a pressure bottle in sequence. Stir and react at 100°C for 4 h. After the reaction is completed, cool to room temperature immediately. Filter to remove the residue, wash the filter cake with dioxane, combine the filtrate, add deionized water to precipitate the solid, filter and dry to obtain organic-soluble corncob lignin.

[0115] (2) Catalyst lignin hydrogenolysis: Weigh 0.1 g of organic soluble corncob lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0116] The yield of monophenol product was calculated to be 21.7 wt.%, of which the yield of 4-propyl syringol was 4.8 wt.%, and the selectivity was up to 22.1%.

[0117] Example 14: CoNC at 190°C -M4 Catalytic Hydrogenolysis of Organosoluble Bagasse Lignin

[0118] The difference between this implementation case and implementation case 5 is that:

[0119] Catalytic lignin hydrogenolysis: weigh 0.1 g of organic soluble corncob lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 190℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Add 5 times the volume of deionized water to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0120] The yield of monophenol product was calculated to be 12.7 wt.%, of which the yield of 4-propyl syringol was 4.2 wt.%, and the selectivity was up to 33.3%.

[0121] Example 15: CoNC at 260°C -M4 Catalytic Hydrogenolysis of Organosoluble Bagasse Lignin

[0122] The difference between this implementation case and implementation case 5 is that:

[0123] Catalytic lignin hydrogenolysis: weigh 0.1 g of organic soluble corncob lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 260℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0124] The yield of monophenol product was calculated to be 23.8 wt.%, of which the yield of 4-propyl syringol was 5.9 wt.%, and the selectivity could reach 24.7%.

[0125] Example 16: CoNC -M4 Catalytic reaction of organosoluble bagasse lignin for 2 hours

[0126] The difference between this implementation case and implementation case 5 is that:

[0127] Catalytic lignin hydrogenolysis: weigh 0.1 g of organic soluble corncob lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 2h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phases are combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0128] The yield of monophenol product was calculated to be 17.5 wt.%, of which 4-propyl syringol was 7.0 wt.%, and the selectivity was 40.2%.

[0129] Example 17: CoNC -M4 Catalytic reaction of organosoluble bagasse lignin for 10 hours

[0130] The difference between this implementation case and implementation case 5 is that:

[0131] Catalytic lignin hydrogenolysis: weigh 0.1 g of organic soluble corncob lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2 The pressure is 1MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 10h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five volumes of deionized water are added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0132] The yield of monophenol product was calculated to be 26.1 wt.%, of which the yield of 4-propyl syringol was 7.2 wt.%, and the selectivity was up to 27.8%.

[0133] Example 18: CoNC under 2MPa hydrogen pressure -M4 Catalytic Hydrogenolysis of Organosoluble Bagasse Lignin

[0134] The difference between this implementation case and implementation case 5 is that:

[0135] Catalytic lignin hydrogenolysis: weigh 0.1 g of organic soluble corncob lignin and 0.1 g of CoNC -M4 The catalyst was placed in a 50 mL batch reactor, and 10 mL of EtOH was added as the reaction solvent. 2 Replace the atmosphere in the reactor (4 times), and finally keep H 2The pressure is 2MPa. After the reactor is closed, the temperature is raised to 230℃ at a rate of 10℃ / min and maintained for 4h. After the reaction is completed, it is immediately cooled to room temperature, the catalyst and the reaction solution are separated by filtration, and the catalyst is washed with EtOH (3mL×3), and the organic phase is combined. A quantitative internal standard solution (dimethyl phthalate) is added to the organic phase, mixed evenly, 1mL of the organic phase solution is taken for further purification, and the product is qualitatively and quantitatively analyzed by GCMS instrument. Five times the volume of deionized water is added to the remaining organic phase to precipitate the solid, and the regenerated lignin can be obtained after filtration and drying. The lignin conversion rate can be calculated by the mass of the reaction substrate lignin and the mass of the regenerated lignin.

[0136] The yield of monophenol product was calculated to be 22.2 wt.%, of which the yield of 4-propyl syringol was 8.0 wt.%, and the selectivity was up to 36.0%.

[0137] Example 19: Catalyst Stability

[0138] The catalyst used in Example 5 was collected and washed with THF (30 mL × 3). After washing, it was dried in a 60°C forced air drying oven to constant weight, and repeated tests were performed with reference to Example 5. After repeated use four times, the catalyst can still maintain a high activity, with a total yield of monophenol of 15.7wt.%, a main product 4-propyl syringol yield of 4.3wt.%, and a selectivity of 27.4%. After only using an organic solvent to wash the catalyst, the catalyst activity decreased slightly during repeated use. After ICP-AES analysis, the cobalt metal content decreased from 0.46wt.% of the fresh catalyst to 0.35wt.%. The carbon content increased slightly, from 70.76wt.% to 73.30wt.%. After simple steam regeneration, the catalyst activity was basically restored, with a total yield of monophenol of 24.3wt.%, and a yield of 4-propyl syringol of 9.9wt.%. By x-ray photoelectron spectroscopy, N 2 Physical adsorption and desorption as well as scanning electron microscopy analysis revealed that the lignin residues and oligomers adsorbed on the surface of the reused catalyst covered the active site Co, making it difficult for it to contact the reaction substrate. The regenerated catalyst fully exposed the active site, which led to the complete recovery of the catalyst activity.

[0139] It can be seen from the above embodiments that the present invention provides a lignin-based cobalt-nitrogen co-doped porous carbon catalyst for catalyzing lignin hydrogenolysis, and selectively preparing monophenolic chemicals mainly based on 4-propyl eugenol. The lignin conversion rate is 75.6% to 94.5%, the total yield of monophenol is 14.2 to 28.8wt.%, the yield of the main product 4-propyl eugenol is 4.1 to 9.9wt.%, and its selectivity is 28.9 to 39.1%. In particular, the catalyst prepared by the present invention does not require the precious metal Ru, the cost of the raw materials used is lower, the catalyst can be prepared by a one-pot method, the preparation process is simple, the catalyst structure is stable, the repeatability is high, the metal utilization rate is significantly improved, and high-pressure hydrogen is not required. The catalyst has a multi-level pore structure, in which the mesopore ratio is 51.9 to 92.9%, which is more conducive to the adsorption of the catalyst to the substrate and enhances the mass transfer effect. The catalytic active center Co mainly exists in the form of a single atom on the catalyst surface, and the highly dispersed active center further increases the probability of the catalyst contacting the substrate, promotes the catalytic effect, and improves the selectivity of the product.

[0140] Compared with Chinese invention patent 202311762765.4, the catalyst uses the precious metal Ru as the active center. Under a 2MPa atmosphere, 250°C catalytic conversion for 12h can obtain 23.9wt.% of a single benzene ring product. The present invention uses transition metal cobalt as the active center, which is more abundant than the precious metal Ru in reserves. At the same time, the main carbon source and nitrogen source of the catalyst are cheap and widely available, so the overall cost of the catalyst is low, which is conducive to industrialization. At the same time, although the cobalt element in the catalyst has a minimum content of only 0.46wt.%, catalytic lignin depolymerization can obtain a total monophenol yield of 28.8wt.%, and the main product 4-propyl thujaol yield is as high as 9.9wt.%. At the same time, the reaction conditions are milder, which solves the problems of high catalyst cost and harsh reaction conditions in the prior art.

[0141] Compared with Chinese invention patent 202111370517.6, although both are lignin-based porous carbon catalysts, the catalyst preparation process is simpler. Specifically, Chinese invention patent 202111370517.6 requires a process of calcining the carrier, impregnating it, and then reducing it, which makes it difficult to accurately control the degree of metal dispersion and the morphology and structure of the catalyst. The present invention prepares the catalyst through a one-pot method, and the catalyst structure is stable and highly repeatable, which is more conducive to industrial production. At the same time, this technical invention has a lower metal content, significantly improves metal utilization, and significantly reduces the cost of catalyst preparation. In Chinese invention patent 202111370517.6, the catalytic conditions need to reach 230°C, 2MPa H 2 The total yield of monophenols was only 22.03 wt.% after 4 h of reaction, of which the yield of 4-propyl syringol was only 7.4 wt.%. In contrast, the present invention only requires 1 MPa H 2Under the above conditions, a total yield of 28.8 wt.% of monophenols can be obtained, of which the yield of 4-propyl syringol reaches 9.9 wt.%. At the same time, the product selectivity is high, and 8.3 wt.% of pure 4-propyl syringol can be obtained by simple column chromatography separation.

[0142] Compared with Chinese invention patent 202311873995.8, the metal in the catalyst of the present invention is uniformly dispersed on the catalyst surface at a single-atom level, the metal exposure surface of the catalyst surface is more, and the pores of the catalyst structure are richer, which effectively improves the contact between the catalytic active center and the substrate lignin, and improves its lignin hydrogenolysis efficiency and selectivity for 4-propylsyringol monomer. The metal content of the catalyst of the present invention is 0.46-10.88wt.%, which is much lower than 29.0wt.% of Chinese invention patent 202311873995.8.

[0143] In general, it can be seen from the above embodiments that the present invention adopts a one-pot method, which does not require the preparation of a carrier-impregnation-reduction process, nor does it require the preparation of MOFs materials and then calcination, and has obvious advantages in the catalyst preparation process; and the catalyst of the present invention uses transition metals as catalytic sites, and the metals are evenly dispersed on the catalyst surface at a single-atom level. The catalyst structure has rich pores, and the gold catalyst has many metal exposed surfaces on the surface, the metal catalytic efficiency is high, the metal content is very low, the catalyst metal content is as low as 0.46wt.%, and the highest is only 10.88wt.%, and the cost of the catalyst has obvious advantages; the above two advantages make the present invention have obvious industrial advantages on the premise of ensuring good conversion efficiency while being beneficial to the preparation of 4-propylsyringol from lignin.

[0144] The implementation methods of the present invention are not limited to the above-mentioned embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing 4-propylsyringol by catalyzing the hydrogenolysis of lignin by cobalt-nitrogen co-doped porous carbon, characterized in that: Using organic soluble lignin as raw material, lignin-based cobalt-nitrogen co-doped porous carbon as catalyst, and small molecule alcohol as reaction medium, stirring reaction is carried out at a hydrogen pressure of 1-2 MPa and a temperature of 190-260°C to selectively hydrogenate the organic soluble lignin into monophenolic chemicals mainly composed of 4-propyl syringol; The lignin-based cobalt-nitrogen co-doped porous carbon is obtained by mixing a precursor and an alkaline pore-forming agent, calcining the mixture in an inert atmosphere at 800-1000° C., cooling, grinding, washing and drying. The precursor is prepared by stirring and dissolving a carbon source and a nitrogen source in deionized water at 60-80° C., adding zinc salt, potassium salt and cobalt salt dissolved in deionized water, stirring at 60-80° C., hydrothermally reacting at 160-200° C. for 8-10 hours, cooling and drying. The carbon source is any one of sulfate lignin, alkali lignin or sodium lignin sulfonate. The nitrogen source is any one of dicyandiamide and melamine.

2. The method for preparing 4-propylsyringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon according to claim 1, characterized in that: The zinc salt is any one of zinc acetate, zinc chloride and zinc nitrate; The potassium salt is any one of potassium acetate, potassium chloride and potassium nitrate; The cobalt salt is any one of cobalt acetate and cobalt chloride.

3. The method for preparing 4-propylsyringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon according to claim 1, characterized in that: The mass ratio of the carbon source to the nitrogen source is 1:3 to 1:5; the mass ratio of the carbon source to the cobalt salt is 1:0.13 to 1:0.62; the mass ratio of the carbon source to the zinc salt is 1:0.33 to 1:0.66; the mass ratio of the carbon source to the potassium salt is 1:0.15 to 1:0.30; the zinc salt, potassium salt and cobalt salt dissolved in deionized water form a metal salt aqueous solution, in which the concentration of total metal ions in water is 50 mmol L -1 ~300mmol L -1 .

4. The method for preparing 4-propylsyringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon according to claim 1, characterized in that: The stirring reaction time at the temperature of 190-260° C. is 2-10 hours; the alkaline pore-forming agent is any one or more of KOH and NaOH; the mass ratio of the carbon source to the alkaline pore-forming agent is 1:0.25-1:0.75; and the stirring time at 60-80° C. is 8-10 hours.

5. The method for preparing 4-propylsyringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon according to claim 1, characterized in that: The cooling involved in the cooling, grinding, washing and drying after calcination at 800-1000°C in an inert atmosphere refers to cooling to room temperature, the grinding involved refers to grinding to a uniform powder without obvious granularity, and the washing involved includes water washing and acid washing. The water washing refers to dispersing the ground product in deionized water, stirring for 2-4 hours, filtering, and then washing the solid with a large amount of water until the filtrate is neutral; the acid washing refers to dispersing the washed product in an aqueous solution of an inorganic acid, stirring for 2-4 hours, filtering to obtain a solid, and then washing the solid with deionized water until the filtrate is neutral; the acid used for the acid washing is any one of sulfuric acid, nitric acid and hydrochloric acid, and the concentration of the acid is 1-2 molL -1 The drying involved is to dry the washed solid in an oven at 50-80°C for 8-12 hours until the sample has a constant weight. The cooling and drying after the hydrothermal reaction at 160-200°C for 8-10 hours refers to cooling to room temperature, and the drying refers to completely removing water in a rotary evaporator at 40-60°C. After the rotary evaporation, the solid obtained is dried in an oven at 50-80°C for 8-12 hours to constant weight; the oven is a forced air drying oven.

6. The method for preparing 4-propylsyringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon according to claim 1, characterized in that: The inert atmosphere is any one of nitrogen, argon and helium; the small molecule alcohol medium is any one of ethanol, methanol and isopropanol; the monophenol chemicals are 4-ethylphenol, ethyl dihydrocoumarate, 4-ethylguaiacol, 4-propylguaiacol, ethyl dihydroferulate and 4-propylsyringol.

7. The method for preparing 4-propylsyringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon according to claim 1, characterized in that: The calcination is carried out in an extractable vacuum tube furnace; the hydrothermal kettle used for the hydrothermal reaction is a stainless steel hydrothermal reaction kettle with an inner lining, and the hydrothermal kettle is provided with a stirring bar, and is stirred and heated in an oil bath pot.

8. The method for preparing 4-propylsyringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon according to claim 1, characterized in that: The organosoluble lignin is obtained by the following extraction method: mixing biomass powder with an extract, reacting at 90-110° C. for 2-4 hours, and cooling to room temperature; filtering to obtain an organic filtrate, adding deionized water to precipitate a solid, filtering and drying to obtain the organosoluble lignin.

9. The method for preparing 4-propylsyringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon according to claim 8, characterized in that: The biomass is derived from any one of bagasse, wheat bran, corn cob, bamboo, birch and poplar; the extract is a mixture of acid and organic solvent; the organic solvent is any one of dioxane and ethanol; the drying after filtering is carried out in a vacuum drying oven, and the drying temperature is 40-60°C.

10. The method for preparing 4-propylsyringol by hydrogenolysis of lignin catalyzed by cobalt-nitrogen co-doped porous carbon according to claim 9, characterized in that: The acid is 1 to 2 mol L -1 any one of hydrochloric acid and sulfuric acid solutions; the ratio of the mass of the biomass powder to the volume of the organic solvent in the extract is 1:3 to 1:5, and the units of mass and volume are g and mL respectively; the ratio of the mass of the biomass powder to the volume of the acid solution is 1:0.8 to 1:1, and the units of mass and volume are g and mL respectively.

Citation Information

Patent Citations

  • Method for preparation of phenolic compound by direct hydrogenolysis of lignin

    CN104276930A

  • Carbon-nitrogen material loaded nickel catalyst with adjustable mesoporous aperture as well as preparation method and application of carbon-nitrogen material loaded nickel catalyst

    CN112547106A

  • Method for preparing 4-ethylphenol by depolymerizing lignin based on liquid phase reforming system

    CN112608219A

  • Method for catalyzing hydrogenolysis of lignin by sodium lignin sulfonate-based porous carbon loaded metal nickel

    CN114230443A

  • Method for preparing cellulose and lignin oil by depolymerizing lignocellulose without exogenous hydrogen

    CN116103949A

Cited By

  • Non-metal nitrogen-doped lignin-based porous carbon material, preparation method thereof and application of non-metal nitrogen-doped lignin-based porous carbon material in catalyzing aldehyde ammonia oxidation to synthesize nitrile

    CN120189965A